Analysis of Different R&D Co-Competition Modes of Asymmetric Duopoly Enterprises under the Uncertainty of R&D Success - Yinghua Song; Xiaoyan Sang; Zhe Wang; Hongqian Xu (Discrete Dynamics in Nature and Society)
The collaborative R&D of new products between enterprises is prone to the “free-rider effect” due to knowledge spillover. To avoid that, this paper establishes a three-stage dynamic game to explore the collaborative R&D co-competition behavior between asymmetric horizontal supplier enterprises. In this paper, we incorporate the uncertainty of R&D success probability into the model and reverse induction is applied to solve it. In the model, two asymmetric enterprises play dynamic games under three modes: complete noncooperation, semicooperation, and complete cooperation. We discuss the sensitivity of various asymmetric factors to the R&D investment level and profit of enterprises. The results indicate that the R&D investment level of supplier enterprises is positively correlated with the absorptive capacity, technology spillover, and R&D success probability, and negatively correlated with the initial R&D investment and innovation efficiency under the three co-competition modes. Especially, when the absorptive capacity of the enterprise or the degree of technological spillover of the other party exceeds a certain value, the profits of the enterprise in the mode of complete noncooperation and semicooperation will intersect, which can easily lead to “free-riding” behavior. It provides a decision-making basis for the direction and extent of enterprises’ R&D efforts. In addition, some methods are proposed to improve the level of R&D investment and increase the income of enterprises under three modes.